Modelo de demanda de dinero para firmas: aspectos teóricos, metodología y resultados (Tema Central) - Vera Lasso, Wilson (2021)
The purpose of this article is to contribute with the theoretical, methodological and empirical elements of the money demand for a company, so that the management of the treasury of firms and financial institutions using a significant flow of liquid monetary resources allows, on one hand, to minimize the opportunity costs of maintaining excess cash and, and on the other hand, to cover their short-term obligations in a timely manner. For this, in a medium-sized software marketing company, the application of the MOV model (Miller, Orr and Vera) of demand for money for firms is proposed, whose theoretical support is the initial approach of Miller and Orr, 1968, in addition to the contribution of Vera, 2004. From the obtained results in this research, it is concluded that efficient liquidity management is possible minimizing transaction costs and maximizing the investment profitability in securities.